Successful Chimeric Antigen Receptor (CAR) T-Cell Treatment in Aggressive Lymphoma Despite Coronavirus Disease 2019 (CoVID-19) and Prolonged Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Replication - Case Report - Nilius-Eliliwi, Verena; Mika, Thomas; Baraniskin, Alexander; Wünnenberg, Max; Maslova, Marina; Boy, Christian; Klein-Scory, Susanne; Schroers, Roland; Vangala, Deepak (Frontiers in Oncology, 2021)
In patients with compromised immune function, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and coronavirus disease 2019 (CoVID-19) impose particular challenges. Especially in hematological malignancies including lymphoma the demands by this novel virus disease are further enhanced during sophisticated treatments such as chimeric antigen receptor (CAR) T-cell therapy. Here, we present the first case of a patient with refractory diffuse-large B-cell lymphoma, who underwent CAR T-cell treatment in the context of SARS-CoV-2. Irrespective of prolonged and active SARS-CoV-2 infection, T-cells were successfully isolated by apheresis and processed to anti-CD19 CAR T-cells (axicabtagene-ciloleucel). In light of the aggressive lymphoma course, lymphodepleting chemotherapy and CAR-T cells were administered in early recovery after oxygen dependent CoVID-19 pneumonia. Except for moderate cytokine release this cellular immunotherapy was well tolerated. Notably, no deterioration of the SARS-CoV-2 infection, however, complete lymphoma response and full clinical recovery were observed. In conclusion, CAR T-cell treatment in aggressive lymphoma in the setting of SARS-CoV-2 infection is feasible and may offer significant therapeutic activity in refractory disease.